2015
DOI: 10.2500/ajra.2015.29.4178
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Rhinosinusitis with Nasal Polyps and Coexisting Asthma: A Systematic Review

Abstract: Both FESS and medical interventions with systemic anti-inflammatory drugs improved nasal outcomes, although their efficacy in relation to the lower airways remains unclear. A low number of studies met inclusion criteria for this systematic review, which emphasizes the need for high-quality trials to explore the treatment of patients with CRSwNP and coexisting asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
1
50
1
1
Order By: Relevance
“…The prevalence of NP among patients with diagnosed CRS in the US varies from 25% to 30% . Additionally, CRS and asthma are strongly associated with a 50% asthma prevalence in patients with CRSwNP …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of NP among patients with diagnosed CRS in the US varies from 25% to 30% . Additionally, CRS and asthma are strongly associated with a 50% asthma prevalence in patients with CRSwNP …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nasal polyposis recurrence is common following surgery, which could also increase patient care costs. As CRSwNP frequently coexists with asthma, medical management may extend further than CRSwNP treatment, increasing patient care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Erythromycin improved nasal symptoms and was superior to ESS in relation to pulmonary outcomes, but they concluded that all nasal outcomes and QOL improved significantly in the surgical studies. Risk of bias for all interventions leads to the strength of evidence to be considered low [55]. In a prospective randomised study, the effect of surgical and medical management (topical corticosteroids, decongestant and alkaline nasal douche) of CRS on concomitant asthma control was investigated.…”
Section: Comparative Evidence Between Medical and Surgical Interventionsmentioning
confidence: 99%
“…Asthma is the most common chronic disease affecting children, and is characterized by reversible airflow obstruction and chronic inflammation of the airways (Quirce et al, 2015;Rix et al, 2015). Asthma is a heterogeneous disease involving both genetic and environmental factors (Custovic et al, 2012).…”
Section: Introductionmentioning
confidence: 99%